The two pore potassium channel THIK‐1 regulates NLRP3 inflammasome activation. Issue 7 (30th March 2022) - Drinkall, Samuel; Lawrence, Catherine B.; Ossola, Bernadino; Russell, Samuel; Bender, Clare; Brice, Nicola B.; Dawson, Lee A.; Harte, Michael; Brough, David
Abstract: The NLRP3 (NLR family, pyrin domain containing 3) inflammasome is a multi‐protein complex responsible for the activation of caspase‐1 and the subsequent cleavage and activation of the potent proinflammatory cytokines IL‐1β and IL‐18, and pyroptotic cell death. NLRP3 is implicated as a driver of inflammation in a range of disorders including neurodegenerative diseases, type 2 diabetes, and atherosclerosis. A commonly reported mechanism contributing to NLRP3 inflammasome activation is potassium ion (K + ) efflux across the plasma membrane. Identification of K + channels involved in NLRP3 activation remains incomplete. Here, we investigated the role of the K + channel THIK‐1 in NLRP3 activation. Both pharmacological inhibitors and cells from THIK‐1 knockout (KO) mice were used to assess THIK‐1 contribution to macrophage NLRP3 activation in vitro. Pharmacological inhibition of THIK‐1 inhibited caspase‐1 activation and IL‐1β release from mouse bone‐marrow‐derived macrophages (BMDMs), mixed glia, and microglia in response to NLRP3 agonists. Similarly, BMDMs and microglia from THIK‐1 KO mice had reduced NLRP3‐dependent IL‐1β release in response to P2X7 receptor activation with ATP. Overall, these data suggest that THIK‐1 is a regulator of NLRP3 inflammasome activation in response to ATP and identify THIK‐1 as a potential therapeutic target for inflammatory disease. Main Points: The NLRP3 inflammasome is implicated as a driver of inflammation in neurodegenerative diseases. THIK‐1 regulates ATP‐induced NLRP3 activation in macrophages and microglia. THIK‐1 is a potential target for limiting inflammation in disease.